Proceso de atención nutricional en paciente femenina embarazada de 36 años de edad con hipertensión gestacional y sobrepeso. - Vera Vite, Kevin Rafael (2022)
Gestational hypertension is the type of hypertension induced by pregnancy and appears for the first time after 20 weeks of gestation, without proteinuria or hematological or biochemical abnormalities. Globally, hypertensive disorders of pregnancy are commonly the second leading cause of direct maternal death. Overweight and obesity are associated with an increased risk of developing a hypertensive disorder of pregnancy and there is an increased risk of maternal-fetal complications when the pregnancy began with overweight or obesity, and also when there is excessive weight gain in the course of pregnancy. The present clinical case deals with a 36-year-old patient with 26 weeks of gestation who arrives at the nutritional consultation gestational hypertension and overweight. Through the evaluation of her nutritional status, it is determined that the patient is at risk of excessive weight gain during pregnancy, so the objective is to control blood pressure and overweight levels in pregnant patients to avoid complications and keep them in optimal ranges through the process of nutritional and clinical care. The nutritional care process corresponding to the four necessary steps that will help achieve the overall goal will be applied. With the results obtained from the nutritional assessment and diagnosis, the eating plan to be followed is prescribed. Finally, it is concluded that after one month of nutritional treatment, favorable results were obtained while the patient was treated at the health center.